Molecular insights into floral scent biosynthesis in Rosa laevigata through transcriptomic and metabolomic analyses - Ru, Jian; Ju, Wen-Bin; Li, Liang-Ying; Deng, Heng-Ning; Liang, Zhen-Long; Tang, Zhong-Yu; Miao, Jia; Zhang, Cheng; Gao, Xin-Fen (Frontiers in Plant Science, 2025)
Rosa laevigata Michx., a member of the genus Rosa in Rosaceae, has large, pure white flowers with a pleasant floral scent, making it a valuable ornamental and aromatic plant. However, the composition and dynamic changes in the abundance of its volatile organic compounds (VOCs) at different developmental stages, as well as the molecular mechanisms regulating floral scent biosynthesis, remain unclear. In this study, we conducted metabolomic and transcriptomic analyses to investigate the composition and abundance changes of VOCs in R. laevigata flowers at three developmental stages. Additionally, we identified key structural genes involved in the floral scent biosynthesis pathways. The results showed that a total of 330 VOCs were identified during the three developmental stages, of which 192 were differential volatile organic compounds (DVOCs), mainly benzenoids/phenylpropanoids and esters. Transcriptomic analysis further identified 8,585 differentially expressed genes, of which 67 were key structural genes related to floral scent biosynthesis. The regulatory network of transcription factors and structural genes revealed that 20 transcription factors were highly associated with floral scent biosynthesis. These findings provide a theoretical basis for the molecular breeding of fragrant germplasm in R. laevigata and contribute to the development of its aromatic industry.